An Overview Of The Knowledge Of Young Women About The Ideal Age For Marriage, Preparation For Family Life And The Impact Of Early Marriage At SMAS Methodist Pancur Batu 2022 - Youfi Rani Brahmana; Risda Mariana Manik; Ermawaty Sialagan (Science Midwifery, 2022)
According to the World Health Organization (WHO), adolescents are children who have reached the age of 10 to 18 years, while according to the National Education Office, it is considered a teenager if a child has reached the age of 10-18 years for girls and 12 to 20 years for boys. This study aims to obtain a clearer and more complete picture of Overview of knowledge about the ideal age of marriage, preparation for family life and the impact of early marriage on young women. This research uses a descriptive method. The sample in this study was 115 female adolescent girls at SMAS Methodist Pancur Batu street. Pancur Batu, Deli Serdang Regency, North Sumatra. The sampling technique is Stratified Random Sampling which is where the sample is taken based on the strata in the population . The research instrument uses a questionnaire in the form of a google form . The results obtain from 31 respondents show that the most who had good knowledge were 18 people 58.06%, knowledgeable enough 8 people 25.82% and the least who had less knowledge are 5 people 16.12%. Respondents' knowledge is good because respondents received more information from education staff or teachers who might be able to help young women to gain knowledge about the impact of early marriage, they also got knowledge and information from social media.